2018
DOI: 10.12688/wellcomeopenres.13940.1
|View full text |Cite
|
Sign up to set email alerts
|

The Liverpool Care Pathway for the Dying Patient: a critical analysis of its rise, demise and legacy in England

Abstract: Background : The Liverpool Care Pathway for the Dying Patient (‘the LCP’) was an integrated care pathway (ICP) recommended by successive governments in England and Wales to improve end-of-life care, using insights from hospice and palliative care. It was discontinued in 2014 following mounting criticism and a national review.  The ensuing debate among clinicians polarised between ‘blaming’ of the LCP and regret at its removal. Employing the concept of ‘boundary objects’, we aimed to address three questions: 1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 75 publications
0
23
0
Order By: Relevance
“…83 The limitations of this view in the context of end-of-life care were illustrated most starkly by the Liverpool Care Pathway, which failed in part because it came to be seen as a mechanistic checklist rather than a nuanced approach to care to be implemented with sensitivity. 89 There are continual warnings that ACP discussions should not be reduced to a tick-box exercise measured by blunt key performance indicators. 2 However, the extent to which nuanced, person-centered implementation of ACP that meets the diverse preferences of patients and carers will be achievable without health system change is unclear, 23 particularly when ACP implementation is largely evaluated by document completion.…”
Section: Discussionmentioning
confidence: 99%
“…83 The limitations of this view in the context of end-of-life care were illustrated most starkly by the Liverpool Care Pathway, which failed in part because it came to be seen as a mechanistic checklist rather than a nuanced approach to care to be implemented with sensitivity. 89 There are continual warnings that ACP discussions should not be reduced to a tick-box exercise measured by blunt key performance indicators. 2 However, the extent to which nuanced, person-centered implementation of ACP that meets the diverse preferences of patients and carers will be achievable without health system change is unclear, 23 particularly when ACP implementation is largely evaluated by document completion.…”
Section: Discussionmentioning
confidence: 99%
“…Yet a closer analysis of the discourse surrounding death and dying presents a very complex picture, and the hesitancy of some people to address and discuss death and dying in some social contexts can be contrasted with the intensity of the advocacy and debate that boils over in others, for example on legalization of assisted dying, or with regard to public debate in the UK about the Liverpool Care Pathway (16)(17)(18)(19). In his survey of Kastenbaum's theory of the "death system" as applied to the USA, Corr concluded that rather than being simply death-denying, American attitudes demonstrate that denial and acceptance of death coexist (20), whilst a systematic review from the UK shows how attitudes vary greatly by age and health circumstances (21).…”
Section: Introductionmentioning
confidence: 99%
“…Within the past 20 years, public consciousness has shifted to a point where palliative and EOL issues are being increasingly discussed publicly; the scrapping of the UK's Liverpool Care Pathway being a prime example. 11 Feedback from end users, such as physicians, caregivers and healthcare providers, might, therefore, be invaluable when crafting and fine-tuning these reactive guidelines in order to directly address critical points that are raised in legal and medical circles. Proactive guidelines, in contrast, might be too generic to precisely identify solutions or guidance on issues that have yet to be identified as important.…”
Section: Discussionmentioning
confidence: 99%